DEVELOPMENT OF INTERACTIVE MULTIMEDIA BASED ON EDUCATIONAL GAME APPLICATIONS IN INDONESIAN LANGUAGE LEARNING FOR GRADE V ELEMENTARY SCHOOL STUDENTS - Zulfikar Amiluddin; Munirah Munirah; Muhammad Akhir (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to examine the prototype, validity, practicality, and effectiveness in the development of interactive multimedia based on educational game applications to improve Indonesian learning in grade V elementary school students. This research was carried out at UPTD SD Negeri 79 Barru with a trial involving 21 students. The method used is Research and Development (R&D) with the Alessi & Trollip development model. The results of this media development prototype research present material not only in the form of text, but also through learning videos, relevant videos, and equipped with interactive quizzes to test students' understanding, so that learning becomes more interesting and interactive. The results of media validation are in the very valid category based on the Gregory test, with a reliability value of 1, as well as materials that also obtain a reliability value of 1. This learning media is practically used in the learning process, based on the results of observations with an average score of 1.00 (implemented category), teacher response questionnaires with an average of 1.00 (implemented categories), and student response questionnaires with an average of 0.99 (implemented categories), so that the total average practicality reaches 0.99%. The effectiveness of the media can be seen from the results of the pretest and posttest scores on the test, where all students achieved learning completeness, proving that this media is effective. This shows that there is an improvement in Indonesian learning outcomes through the use of interactive multimedia based on educational game applications.